The Effect of Logistics Costs and Product Prices on the Export Volume at PT Mas Sumbiri I Kendal Regency - Muhammad Yazid Ulwan; Sri Marhaeni Salsiyah; Taviyastuti - Taviyastuti (Admisi dan Bisnis, 2019)
The purpose of this study is to analyze the influence of logistic cost and product price toward export volume of PT MAS Sumbiri I. PT MAS Sumbiri I is an export oriented garment company. This study used secondary data in the form of time series data from January 2016 to December 2018. Data analysis method used in this research is multiple linear regression equipped with a descriptive analysis, a classic assumption test (tests for normality, heterokedasticity, multicollinearity, autocorrelation, and linearity) and hypothesis testing (F-test, T-test, and coefficient of determination). The classic assumption test shows that there is no problem with the variable being tested. The F-Test shows that logistic cost and product price simultaneously and significantly influence the export volume of PT MAS Sumbiri I. The T- test shows that logistic cost and product price have a negative and significant effect toward export volume. Based on the coefficient of determination, the logistic cost and product price have an effect of 46.3% on the export volume of PT MAS Sumbiri I while the remaining 53.7% is influenced by other variables outside this study